2020
DOI: 10.29333/aquademia/8494
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Coronavirus Disease 2019 (COVID-19) on College and University Students: A Global Health and Education Problem

Abstract: The origin of the coronavirus disease 2019 (COVID-19) in Wuhan China has been reported to be one of the lethal pandemics the world has ever faced. Though the first case was reported in December 2019, COVID-19 spread so rapidly to the majority of countries by March 2020 and was declared a global pandemic by the World Health Organization. COVID-19 pandemic led to increased morbidity and mortality within a very short period of time. COVID-19 pandemic caused schools, colleges, and universities to come to a closure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 10 publications
0
39
0
Order By: Relevance
“…(2020) similarly reported that students experienced challenges with regards to learning clinical skills due to a lack of clinical placements [32]. Evidence has shown that University and College students were worried about their academic progress because of COVID-19 and the introduction of online learning [33,34]. Similarly, a study by Charles et al (2020) on alcohol abuse among college students during the COVID pandemic reported that students experienced signi cant educational disruptions as the pandemic interfered with their academic functioning [35].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…(2020) similarly reported that students experienced challenges with regards to learning clinical skills due to a lack of clinical placements [32]. Evidence has shown that University and College students were worried about their academic progress because of COVID-19 and the introduction of online learning [33,34]. Similarly, a study by Charles et al (2020) on alcohol abuse among college students during the COVID pandemic reported that students experienced signi cant educational disruptions as the pandemic interfered with their academic functioning [35].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a study by Charles et al (2020) on alcohol abuse among college students during the COVID pandemic reported that students experienced signi cant educational disruptions as the pandemic interfered with their academic functioning [35]. This is because the closure of tertiary-level educational institutions suspended face-to-face teaching-learning sessions hence interrupting the regular ow of academic programs [34,36]. Some schools had to postpone or cancel the students' examinations [37].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Coronavirus disease 2019 (COVID-19) is a global public health problem that originated from Wuhan city of Central China's Hubei Province in December 2019 (Guo et al, 2020;Kasanga et al, 2020). COVID-19 is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-12) Guo et al, 2020;Mudenda et al, 2020a). COVID-19 spread rapidly from China to the rest of the world and was declared a global pandemic by the World Health Organization (WHO) on the 11 th March 2020 (ECDC, 2020;Mudenda, 2020).…”
mentioning
confidence: 99%